2003
DOI: 10.1525/si.2003.26.4.645
|View full text |Cite
|
Sign up to set email alerts
|

Chrysalid Goffman: A Note on “Some Characteristics of Response to Depicted Experience”

Abstract: Goffman's first substantial sociological work, his M.A. thesis entitled “Some Characteristics of Response to Depicted Experience,” has hitherto escaped critical commentary. Inspection of the thesis yields insights into the early development of Goffman's sociology. It shows that Goffman's later dismissal of positivistic and experimental approaches, his suspicion of interview methods, and his valorization of observational data have their origins in his research experiences in late 1940s Chicago while he worked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…2. Although Goffman avoided articulating concrete ethnographic guidelines, G. W. H. Smith (2003) demonstrated that Goffman conveyed a sense of fundamental principles through his assessment of the methodological deficiencies of his master's thesis. Furthermore, Smith showed how the logic of Goffman's inquiry took initial form in the master's thesis.…”
Section: Notesmentioning
confidence: 99%
“…2. Although Goffman avoided articulating concrete ethnographic guidelines, G. W. H. Smith (2003) demonstrated that Goffman conveyed a sense of fundamental principles through his assessment of the methodological deficiencies of his master's thesis. Furthermore, Smith showed how the logic of Goffman's inquiry took initial form in the master's thesis.…”
Section: Notesmentioning
confidence: 99%
“…Commentators have seen it as systematic (Giddens 1988) and as discontinuous (Sharrock 1976). Some see a general micro theory in his work (Manning 1992), while others find “a much more structural image than we would receive from most symbolic interactionists” (Ritzer and Goodman 2004:225; see also Chriss 1995:178; Smith 2003:655). Maybe all these claims are justified.…”
mentioning
confidence: 99%
“…Takođe, nije na odmet pomenuti da je 1949. godine objavljen Hjuzov prevod Zimelovog teksta (Simmel 1910(Simmel /1949, što dodatno svedoči o povezanosti Zimel-Hjuz-Gofman. Nije tačno da je Hjuz preveo i tekst Simmel 1908Simmel /1965, kao što piše Smith 2003. Blumer je doveo Gofmana na Berkli, jer je i sam doveden iz Čikaga kako bi izgradio najjači mogući departman, i za nekoliko godina broj osoblja je porastao sa šest na više od dvadeset. U tom smislu može se reći da je Berkli početkom šezdesetih godina sadržao ono najbolje od Čikaga, Kolumbije i Harvarda i bio je verovatno jedini veliki i važan departman u kojem nisu dominirale jedna ili dve ličnosti u intelektualnom smislu, kao što nije dominirala jedinstvena metodologija ili teorijski pristup.…”
Section: š 88unclassified
“…Takođe, ponekad su odgovori toliko oskudni da bilo kakva poređenja, a kamoli statističko testiranje, nisu ni moguća -sve validacije su (ukoliko su uopšte moguće) indirektne i javlja se problem regresije validacije validacije itd. I konačno, povezivanje odgovora s karakteristikama ličnosti o kojima je govorio Frojd takođe je arbitrarno i cirkularno, jer istraživač jednim odgovorom ispitanika vrši validaciju drugog (Smith 2003). To znači da je sasvim osnovana sumnja da li TTA uopšte može da otkrije bilo kakvog "unutrašnjeg čoveka" i zaključak je da ne može da se koristi kao "samodovoljni instrument u sistematskom istraživanju" (Goffman 1949, 19).…”
unclassified
See 1 more Smart Citation